Clinicо-morphological diagnostics and surgical treatment of paraduodenal pancreatitis - V. H. Yareshko; V. O. Tumanskyi; Yu. O. Mikheiev; O. M. Kiosov; A. O. Steshenko; N. O. Yareshko; A. V. Kanaki (Zaporozhye State Medical University, 2020)
Paraduodenal pancreatitis (PDP) is a rare disease that develops as a result of chronic inflammation of the ectopically located pancreas in the duodenal wall. Aim. Present our own observations of paraduodenal pancreatitis as a rare pathological condition, its clinical and pathomorphological manifestations, methods of diagnosis and surgical treatment. Materials and methods. An analysis of clinical and instrumental studies and the results of surgical treatment was carried out in eight patients with PDP, who underwent pancreatoduodenal resection in the clinic of surgery and minimally invasive technologies of Zaporizhzhia State Medical Academy of Postgraduate Education of the Ministry of Health of Ukraine and in the multidisciplinary clinical hospital VITACENTER (Zaporizhzhia) in 2015-2019 (6 patients), gastric resection according to Billroth 2 (1 patient), one patient refused surgery. All patients were examined by laboratory methods and modern methods of radiation diagnostics, pathomorphological examination of the operating material was performed in the pathological department of the Zaporizhzhia Regional Pathological Bureau. Paraffin sections for histopathological examination were stained with hematoxylin and eosin and analyzed using Leica DM2000Led microscope (Germany) with Leica MC190HD camera. Results. Preoperative diagnosis of PDP was established in 7 (87.5 %) patients, in 1 case, before the operation, the diagnosis was made of cystic tumor of the head of the PO. A characteristic feature of PDP on computer tomography was the presence of a thickened fibrous plate between the head of the pancreas (RV) and the duodenum (DPC), more pronounced in the venous phase, and the presence of cystic formations in the paraduodenal zone. Endoscopic examination revealed deformity with stenosis or submucosal formation in the descending part of the duodenum. Endoscopic ultrasound examination revealed a thickening of the duodenum wall with the presence of cystic formations. In macroscopic examination of the removed pathology specimen, the walls of the duodenum were thickened, with cicatricial changes and cystic cavities. The main pathological sign of PDP was the presence of ectopic foci of pancreatic acinar tissue and clusters of abnormal pancreatic ducts of various sizes with periductal chronic inflammation found in 4 (57.2 %) cases in the fibrously changed thickened wall of the duodenum. In all cases, in the fields of fibrosis and chronic inflammation, cysts of various sizes were found: ductal cysts lined with ductal epithelium, and acinar cysts without epithelial lining with thickened connective tissue walls (encapsulated foci of enzymatically self-destroyed pancreatic tissue). In 5 (62.5 %) patients in the area of pancreatic ectopia microscopy Brunner's gland hyperplasia was revealed. In 6 (75 %) patients, chronic inflammation and dense fibrosis in the region of the pancreato-duodenal sulcus was revealed, as well as chronic inflammation and peri-intralobular fibrosis of the pancreatic head adhesion to the duodenum. Complications after pancreatoduodenectomy were observed in 2 (28.5 %) patients in the form of gastrostasis (type B according to ISGPS) and pancreatic fistula (type B according to ISGPF). In the long-term period, there was an improvement in the condition of 2 patients with stabilization of weight and an improvement in the functional state according to the scales of the SF-36 and EORTIC questionnaires. In other patients, the follow-up period does not exceed 1 year. Conclusions. The optimal method of clinical diagnosis of paraduodenal pancreatitis is endoscopic ultrasound, and its pathomorphological confirmation is the presence of ectopic pancreatic tissue or cysts in the duodenal wall, chronic inflammation and fibrosis, Brunner's gland hyperplasia, chronic inflammation in the area of pancreato-duodenal inflammation and fibrosis in the pancreatic head adhesion. The most justified method of surgical treatment of paraduodenal pancreatitis is still pancreatoduodenectomy.